2022
DOI: 10.3390/v14040672
|View full text |Cite
|
Sign up to set email alerts
|

Human Adenovirus Type 26 Induced IL-6 Gene Expression in an αvβ3 Integrin- and NF-κB-Dependent Manner

Abstract: The low seroprevalent human adenovirus type 26 (HAdV26)-based vaccine vector was the first adenovirus-based vector to receive marketing authorization from European Commission. HAdV26-based vaccine vectors induce durable humoral and cellular immune responses and, as such, represent a highly valuable tool for fighting infectious diseases. Despite well-described immunogenicity in vivo, the basic biology of HAdV26 still needs some refinement. The aim of this study was to determine the pro-inflammatory cytokine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…There are two main pathways through which this reactivation may occur. Firstly, both human IL-6 and the KSHV-encoded homolog vIL-6 have been shown to reactivate KSHV [ 4 ]. Studies have demonstrated that adenovirus vector infection of human epithelial cells induces the expression of pro-inflammatory cytokines, particularly IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…There are two main pathways through which this reactivation may occur. Firstly, both human IL-6 and the KSHV-encoded homolog vIL-6 have been shown to reactivate KSHV [ 4 ]. Studies have demonstrated that adenovirus vector infection of human epithelial cells induces the expression of pro-inflammatory cytokines, particularly IL-6.…”
Section: Discussionmentioning
confidence: 99%